Intergovernmental planning and budgeting in Zimbabwe: learning the lessons of the past (Commonwealth Journal of Local Governance, 2018)
In Zimbabwe, the Prime Minister’s Directives on Decentralisation and Development of 1984 and 1985, together with the Provincial Council and Administration Act 1985, constitute the foundation for post-independence attempts to ensure effective governance. The Directives provided for the establishment of hierarchical structures and mechanisms to coordinate government activities, including development planning at various levels of government. This paper asks whether these structures and mechanisms have been effective in promoting ‘sound’ intergovernmental planning and budgeting, and whether they are still relevant given that in 2013 Zimbabwe adopted a new Constitution with greater promises, visions and demands than its predecessor, the Lancaster House Constitution. The paper argues that the adoption of a new Constitution provides a valuable opportunity to reform the intergovernmental planning and budgeting process, which to date has proved ineffective in fostering integrated and coherent effective governance.